2016
DOI: 10.1159/000452880
|View full text |Cite
|
Sign up to set email alerts
|

Klotho/FGF23 Axis in Chronic Kidney Disease and Cardiovascular Disease

Abstract: FGF23 may also contribute to CVD. Prevention of Klotho decline, reactivation of endogenous Klotho production, or supplementation of exogenous Klotho attenuate renal fibrosis, retard CKD progression, improve mineral metabolism, ameliorate cardiomyopathy, and alleviate vascular calcification in CKD. However, the poor CVD outcome after depletion of FGF23 with FGF23 antibody stimulates the generation of a more specific inhibitor of FGF23 for CKD treatment. Key Message: Klotho/FGF23 may not only be diagnostic and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 105 publications
3
135
0
9
Order By: Relevance
“…Klotho is antiaging protein that is highly expressed in renal tubular epithelium of normal kidney, which is suppressed in the elderly and in patients with CKD. 112,113 Klotho is present as full-length, transmembrane protein or secreted, soluble form. Both membranous and soluble forms of Klotho can bind with multiple Wnt ligands and represses their target genes transcription.…”
Section: Wnt Signaling and Kidney Diseasesmentioning
confidence: 99%
“…Klotho is antiaging protein that is highly expressed in renal tubular epithelium of normal kidney, which is suppressed in the elderly and in patients with CKD. 112,113 Klotho is present as full-length, transmembrane protein or secreted, soluble form. Both membranous and soluble forms of Klotho can bind with multiple Wnt ligands and represses their target genes transcription.…”
Section: Wnt Signaling and Kidney Diseasesmentioning
confidence: 99%
“…Clinically, uremic cardiomyopathy is characterized by cardiac arrest or sudden death, left ventricular hypertrophy, cardiac fibrosis, congestive heart failure, and so on [4-6]. In addition to traditional risk factors such as smoking, hypertension, diabetes, anemia, and volume overload, Klotho deficiency also plays an important role because soluble Klotho (s-Klotho) is a circulating substance exerting multiple systemic biological actions on distant organs, such as directly protecting cells against a variety of insults including hypoxia, hyperoxia, oxidative stress, and cytotoxic medication and suppressing apoptosis [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…The Klotho/FGF23 axis is identified as a target for kidney clinics, and Klotho/FGF23 is a prognostic biomarker for CKD and CVD . The presence of Klotho in vascular walls is unclear; however, all the experiments have shown that Klotho prevents VC development.…”
Section: Discussionmentioning
confidence: 99%
“…The Klotho gene encodes a 130‐kDa single‐channel transmembrane protein with a short cytoplasmic domain (10 amino acids) that is primarily expressed in the kidney . FGF23 was identified as a phosphaturic hormone and mainly produced by osteocytes in the bone . Klotho significantly enhances the ability of FGF23 and functions as a cofactor essential for activation of FGF signaling by FGF23 .…”
Section: Introductionmentioning
confidence: 99%